Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1371/journal.pone.0221467
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of a community-based, type 2 diabetes prevention programme on health-related quality of life. The DE-PLAN study

Abstract: Background and aimsThe DE-PLAN was a European multicenter study, with the primary objective of testing whether a community-based lifestyle modification programme could serve as a means of primary prevention for type 2 diabetes (T2D) in high-risk individuals (based on the FINDRISC questionnaire). The aim of this study was to examine the impact of a 1-year community-based lifestyle intervention on health-related quality of life (HRQOL) in individuals from four participating European centers (Athens, Barcelona, K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 55 publications
1
14
0
1
Order By: Relevance
“…DM complications, such as diabetic neuropathy [3], may affect health-related quality of life (HRQoL). One instrument to assess the HRQoL in T2DM patients [4,5] is the 15-D questionnaire, which consists of 15 sections. In addition, it is important to know the foot health status of patients, that may be measured using different tools.…”
Section: Introductionmentioning
confidence: 99%
“…DM complications, such as diabetic neuropathy [3], may affect health-related quality of life (HRQoL). One instrument to assess the HRQoL in T2DM patients [4,5] is the 15-D questionnaire, which consists of 15 sections. In addition, it is important to know the foot health status of patients, that may be measured using different tools.…”
Section: Introductionmentioning
confidence: 99%
“…Just recently, results were published concerning a positive effect on quality of life [11], but no aggregated results from the study have been reported so far. However, some centres have reported local results from the intervention [11][12][13][14], and the results are clearly related to the intensity of the intervention, showing that the more resources, the more effective the intervention [12]. To help and support individuals with prediabetes in primary care, thus, a more intense intervention than group sessions seems to be needed.…”
Section: Discussionmentioning
confidence: 98%
“…The most ambitious diabetes prevention programme was initiated in Finland through the "Diabetes in Europe-Prevention using Lifestyle, Physical Activity and Nutritional Intervention", i.e., the DE-plan, where different European countries are testing whether the DPS can be implemented in existing health care systems [10]. Just recently, results were published concerning a positive effect on quality of life [11], but no aggregated results from the study have been reported so far. However, some centres have reported local results from the intervention [11][12][13][14], and the results are clearly related to the intensity of the intervention, showing that the more resources, the more effective the intervention [12].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, given that diabetes being with such high incidence rate and mortality worldwide, especially in China [42,43] and hypoglycemia had such serious adverse effects on the diabetics' living quality, effective approaches must been taken, particularly the measurements of decreasing the risk of iatrogenic hypoglycemia. On the one hand, medical staff should carry out health education on diabetes [44], which can learn from Karamanakos's [45] advocacy of community-based intervention for diabetes to carry out one-to-one guidance to strengthen blood glucose management and reduce the incidence of hypoglycemia. On the other hand, doctors should strengthen the screening of anxiety and depression in diabetics [46].…”
Section: Discussionmentioning
confidence: 99%